Comprehensive Oral Cancer Examination of the Extra-oral and Intra-oral Regions of the Head and Neck - Nereyda Polo Clark; Pamela R. Sandow (Association of American Medical Colleges, 2012)
Abstract Introduction The resource was created to as a handout to assist the student with note-taking while watching the video from Oral Cancer Screening Task Force. The purpose was to learn how to perform an oral cancer screening in a systematic manner. This particular video was selected as it was available, extremely concise, professionally made, and included all aspects of the examination. Supplemental information is provided in the document and includes descriptions of the steps, visual representation of the steps, clinical pictures showing the anatomical area labeled with its name, and common pathological conditions for the area. Methods The fourteen page tutorial is a detailed description of the steps in the extra-oral and intra-oral examination done as part of the oral cancer exam, including the pertinent cranial nerves. Each region is identified in a systematic manner, including an image of the area and identification of structures. Additionally, the steps are concisely presented, identifying possible findings and corresponding images of pathology. Results Utilizing this handout and video, the students have learned a greater amount of information. Additionally, when testing the students a year later on the oral cancer screening procedure, their retention was 90%. Discussion This tutorial assists dental, allied health students, and medical students with the oral cancer examination process. The tutorial can also be used as a follow-along handout in the preclinical setting when practicing the examination.